3D printed biofunctionalized scaffolds for microfracture repair of cartilage defects. (December 2018) - Guo, Ting; Noshin, Maeesha; Baker, Hannah B.; Taskoy, Evin; Meredith, Sean J.; Tang, Qinggong; Ringel, Julia P.; Lerman, Max J.; Chen, Yu; Packer, Jonathan D.; Fisher, John P.
Abstract: While articular cartilage defects affect millions of people worldwide from adolescents to adults, the repair of articular cartilage defects still remains challenging due to the limited endogenous regeneration of the tissue and poor integration with implants. In this study, we developed a 3D-printed scaffold functionalized with aggrecan that supports the cellular fraction of bone marrow released from microfracture, a widely used clinical procedure, and demonstrated tremendous improvement of regenerated cartilage tissue quality and joint function in a lapine model. Optical coherence tomography (OCT) revealed doubled thickness of the regenerated cartilage tissue in the group treated with our aggrecan functionalized scaffold compared to standard microfracture treatment. H&E staining showed 366 ± 95 chondrocytes present in the unit area of cartilage layer with the support of bioactive scaffold, while conventional microfracture group showed only 112 ± 26 chondrocytes. The expression of type II collagen appeared almost 10 times higher with our approach compared to normal microfracture, indicating the potential to overcome the fibro-cartilage formation associated with the current microfracture approach. The therapeutic effect was also evaluated at joint function level. The mobility was evaluated using a modified Basso, Beattie and Bresnahan (BBB) scale. While the defect control group showed no movement improvement over the course of study, all experimental groups showed a trend of increasing scores over time. The present work developed an effective method to regenerate critical articular defects by combining a 3D-printed therapeutic scaffold with the microfracture surgical procedure. This biofunctionalized acellular scaffold has great potential to be applied as a supplement for traditional microfracture to improve the quality of cartilage regeneration in a cost and labor effective way.